Экономика и искусство - Суименко, Е. (Iнститут соціології НАН України, 2009)
The article written in a genre of sociological essays is devoted to the analysis of correlation, co-operation and functional prerogatives of two types of human attitude to the world - material-transformational (productional-economic) attitude and reflectional (artistical-aesthetic) attitude. Each of these two types of attitude is historically necessary within existence and development of human society. Both of them are considered by the author as an opposition of "negation" (destruction of the natural world fragments by the acts of production and consumption) and "detainment" (spirituality, image-bearing and conceptual reflection of the world around). In a hypothetical form, the author presents an idea of undulating character of human history, in which alternately prevail both "negation" and "detainment". Accordance to this supposition, the spiritual-reflecting attitude must be prevailing in the "post- economic society". Its homoeostatic properties will make it possible to rehabilitate and revivify the natural world and will enable it to "rest" after the exhausting race of commodity production.